Analysis of the Financial Independence Ratio of Makassar City Government During the Second Term of Mohammad Ramdhan Pomanto's Leadership - Khalimatussa’diah, Khalimatussa’diah; Haliah , Haliah (PT FORMOSA CENDEKIA GLOBAL, 2025)
Local governments play a key role in national development through independent financial management. Regional autonomy in Indonesia aims to enhance public services and regional resource management. This study analyzes the financial independence of Makassar City during Mayor Mohammad Ramdhan Pomanto's second term using financial ratios. The quantitative descriptive method evaluates the independence, effectiveness, efficiency, and financial growth based on Makassar's APBD data. Results show fluctuating financial performance, with a moderate financial independence ratio indicating reliance on central government funds. The study highlights the need for improved PAD management and resource optimization to enhance fiscal independence and support sustainable development.